Erratum to: Work Stress, Organizational Commitment, and Turnover Intention: The Intervening Role of Work Satisfaction - JABM Editorial (Jurnal Aplikasi Bisnis dan Manajemen)
Correction to: Marlapa E, Endri E. 2024. Work Stress, Organizational Commitment, and Turnover Intention: The Intervening Role of Work Satisfaction. Jurnal Aplikasi Bisnis dan Manajemen (JABM), 10(2): 503. https://doi.org/10.17358/jabm.10.2.503